ANALISIS TRANSFORMASI PENERAPAN E-BUSINESS PADA UMKM UNTUK MENINGKATKAN DAYA SAING DI ERA DIGITAL - Yuanda, Landes; Kristriantoro, Febby (STAI Sulthan Syarif Hasyim, 2024)
The implementation of e-business has become a crucial element in business transformation in the digital era, especially for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs, which play a significant role in the national economy, face various challenges, such as limited market access and operational inefficiency. This study aims to analyze the e-business transformation process in MSMEs and its impact on enhancing competitiveness in the digital age. The research uses a qualitative method with a literature review approach to explore various theories and empirical findings related to e-business adoption and digital transformation strategies. The results show that the implementation of e-business can improve efficiency, expand market access, and strengthen customer relations. However, challenges faced by MSMEs, such as limited resources and technological skills, require support from the government and the private sector. In conclusion, e- business adoption combined with proper transformation strategies can significantly enhance MSMEs' competitiveness in both local and international markets.